The Impact of Covid-19 Pandemic on the Interest in Family Planning among Couples of Childbearing Age - Nyna Puspita Ningrum; Rizka Esty Safriana (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2023)
The population growth rate in Indonesia has been declining recently. Family Planning program is an initiative of the Indonesian government that has been running since 1980. It has been successful in reducing the population growth rate. The number of children a woman has during her reproductive period is known as the total fertility rate. However, the Covid-19 pandemic has prompted worries about the rising birth rate as a result of the disruption of contraceptive services. In order to assist the government in gathering information on family planning acceptors among couples of childbearing age in Indonesia and to serve as a resource for courses on reproductive health and family planning, this study aims to determine the impact of Covid-19 pandemic on the interest in family planning among couples of childbearing age. This was a quantitative analytical study with a one-shot case study design. The study populations involved 137 participants of couples of childbearing age with children. All completed the questionnaire; 112 of them were selected using the total sample approach in accordance with the inclusion and exclusion criteria. Data obtained as the results of survey were tested for validity using the product moment validity test. Chi-square analysis was applied which obtained a p value of 0.003 or less than 0.05. It can be concluded that there was a strong correlation between family planning implementation and participation during the Covid-19 pandemic in September to December 2020. According to the study finding, couples of childbearing age were less interested in family planning as a result of the Covid-19 pandemic.